CKAMP44 modulates integration of visual inputs in the lateral geniculate nucleus - Chen, Xufeng; Allen, Kevin (Nature Communications, 2018)
The function of receptor desensitization in vivo is not well understood. Here, the authors show that deletion of CKAMP44, an AMPAR auxiliary protein that modulates desensitization of AMPAR currents, affects synaptic facilitation at retinogeniculate synapses and visually-evoked firing in awake mice.
Gesehen am 18.04.2019